Parameter Analysis of Fluid-Solid Coupling for Wet Brake Disc - Xunjia Zheng; Tianhong Luo; Ce Jia (Institute of Advanced Engineering and Science, 2014)
Due to the poor conditions of wet brake cooling and the high temperature of the working characteristics, this paper intended to introduce the oil film vadose between the brake linings, considered the variation of volume of grooves on the friction plate, and then proposes the three-dimensional transient dynamic response of fluid-solid coupling mathematical model. By parameter analysis of the disc transient thermal stress field distribution on the friction plate, and according to the real dimension of the brake disc, the distribution of the temperature and the stress of the wet brake disc during the braking are analyzed, the variation of temperature field and stress field in friction plate are obtained. The data curves shown the temperature and the stress are coupled. Finally, the results shows that the mathematical model is effective and feasible.